2012
DOI: 10.1111/j.1365-2621.2012.03184.x
|View full text |Cite
|
Sign up to set email alerts
|

Liposomes encapsulating beta‐carotene produced by the proliposomes method: characterisation and shelf life of powders and phospholipid vesicles

Abstract: Summary The objective of this study was to investigate the feasibility of producing proliposomes incorporating beta‐carotene by spray drying and to assess the capacity of the liposomes produced by the hydration of the dry phospholipid particles to preserve the encapsulated carotenoid. Powders containing beta‐carotene, hydrogenated phosphatidylcholine and sucrose were obtained and characterised in terms of crystallinity, morphology, thermal behaviour, density, solubility and hygroscopicity. The preservation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(38 citation statements)
references
References 42 publications
1
25
0
8
Order By: Relevance
“…Liposomes can encapsulate hydrophobic compounds inside its bilayer membrane and hydrophilic compound inside its core [21]. Some evidences have demonstrated that liposome is able to encapsulate beta-carotene and vitamin C singly [18,19,26]. Liposome is mostly built up by amphiphilic molecules such as phospholipids [27].…”
Section: Introductionmentioning
confidence: 99%
“…Liposomes can encapsulate hydrophobic compounds inside its bilayer membrane and hydrophilic compound inside its core [21]. Some evidences have demonstrated that liposome is able to encapsulate beta-carotene and vitamin C singly [18,19,26]. Liposome is mostly built up by amphiphilic molecules such as phospholipids [27].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of organic acids in the matrices of preservation and other compounds such as hydrogen peroxide contained in unadulterated honey can be attributed to the 2002;Bang et al, 2003;Ferreira et al, 2009). Betacarotene preserved in nitrogen (NBC), which was a control, did not show a significant difference in levels of preserved beta-carotene as an inert medium doesn't allow degradation (Nyambaka and Ryley, 2001;Moraes et al, 2013).…”
Section: Levels Of Beta-carotene With Preservationmentioning
confidence: 99%
“…Some efforts have been reported for the preservation of beta-carotene and these include encapsulation in lipid-based matrices and storing under eISSN: 2550-2166 © 2017 The Authors. Published by Rynnye Lyan Resources vacuum or in an inert medium such as nitrogen gas (Nyambaka and Ryley, 2001;Moraes et al, 2013). Such methods are expensive and thus hindering availability of beta-carotene to the needy in society.…”
Section: Introductionmentioning
confidence: 99%
“…Essas perdas de bioativo podem ser consideradas relativamente baixas, fato que é considerado importante, uma vez que o β-caroteno possui baixa estabilidade à oxidação. A oxidação do β-caroteno por fatores como a alta temperatura e a absorção da luz, foram evitadas, uma vez que as amostras foram armazenadas sob refrigeração (~7ºC) e protegidas na ausência de luz, contribuindo para a sua estabilidade (SILVA et al, 2011;MORAES et al, 2013). Outro fator relevante consiste na composição do fosfolipídio utilizado na produção das dispersões, contendo 98% de fosfolipídio hidrogenado, impedindo a peroxidação das suas cadeias de hidrocarboneto.…”
Section: Incorporação E Preservação Do β-Caroteno Nos Lipossomasunclassified
“…Assim pode-se considerar que praticamente não houve oxidação do β-caroteno por tais motivos. A pequena perda de β-caroteno encapsulado, portanto, pode ser explicada, assim como no caso dos lipossomas estabilizados com goma xantana, por dois fatores: (i) a lenta peroxidação do fosfolipídio e (b) a lenta difusão de agentes oxidantes através da membrana fosfolipídica (MORAES et al, 2013). A presença dos agentes oxidantes provavelmente ocorreu, assim como no caso do uso da goma xantana como espessante, devido ao uso da temperatura de 65 C durante etapa de hidratação dos pró-lipossomas.…”
Section: 30% Gx (C)unclassified